A new infrageneric classification and synopsis of the genus Vanilla Plum. ex mill. (Orchidaceae: Vanillinae) - Soto Arenas, Miguel A.; Cribb, Phillip (Lankesteriana: International Journal on Orchidology, 2013)
An updated, annotated checklist of the species of the genus Vanilla is presented, with information on nomenclature, distribution, literature and examined specimens. A key for the determination of the species is included. A new proposal of infrageneric classification of Vanilla is provided.